Social representations of children and its impact on the protection of their rights - Barletta Villarán, María Consuelo (2017)
The purpose of this paper is to approach the social representations present in the imaginary in relation to who children are and their role in society. This is coupled with their primary caregivers, such as family members, denying them their rights, thus proving how difficult it is to consolidate their position as legal subjects in Peruvian society, which continues to hold on to conceptions that make them culturally invisible and distort the respect to their dignity.